COVID-19 pandemic challenges: on the way to overcome obstacles in realization of PAH-specific therapy treatment goals - E. A. Rezukhina; I. Z. Korobkova; N. M. Danilov; V. V. Gramovich; T. V. Martynyuk (Евразийский Кардиологический Журнал, 2021)
Our observation demonstrates a case of a 40-year-old female with idiopathic pulmonary arterial hypertension World Health Organization functional class III, who was admitted to NMRC of Cardiology repeatedly due to disease progression including dyspnea worsening and exercise tolerance decrease after previous COVID-19 infection on riociguat (7.5 mg daily), macitentan (10 mg daily) and selexipag (1600 mcg daily) therapy. Clinical examination demonstrated high-risk status according to the expected 1-year mortality. Due to unreleased treatment goals and high-risk status, we performed transition from selexipag to inhale iloprost. After therapy escalation the patient demonstrated a significant improvement in clinical condition, dyspnea reduction and exercise tolerance increase. The current treatment strategy for pulmonary arterial hypertension is based on regular multiparametric risk stratification approach in PAH patients. The impact of COVID-19 may become an important cause of clinical worsening in PAH patients during COVID-19 pandemic. Directed on vasodilatation and antiproliferation mechanisms of action of PAH-specific drugs are supposed to be protective in COVID-19 patients. However, the probability of clinical worsening in PAH patients despite PAH-specific therapy intake needs to be closely monitored to perform timely treatment correction in order to achieve low-risk status and to improve the prognosis of PAH patients.